Tantangan Penerjemah Pemerintah di Era VUCA - Farah Sarayusa (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2020)
This article examines examines challenges faced by Indonesian Government Translators who works at Arsip Nasional Republik Indonesia (English: National Archives of Indonesia). Arsip Nasional Republik Indonesia, abbreviated as ANRI, is one of non-department government agencies that specialized on archives. This article applies the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) faced by all Indonesian Government Translators who works at Arsip Nasional Republik Indonesia when they do their principal duties and their functions. This article was conducted in a qualitative approach with case study as a research method. The primary data was obtained through in-depth interviews and observations, while the secondary data was obtained from document studies. The results of this article are recommendations are suggested to be implemented in Arsip Nasional Republik Indonesia as the institution itself as well as Sekretariat Kabinet Republik Indonesia (English: Cabinet Secretariat of the Republic of Indonesia ) as fostering institution for Indonesian Government Translators as an effort to empower and strengthen the position of Indonesian Government Translators.